Cognitive dysfunction in drug-naïve late-onset temporal lobe epilepsy - Sekimoto, Masanori; Kato, Masaaki; Muramatsu, Reimi; Onuma, Teiichi (Epilepsy & behavior, 2023)
•We examined cognitive function in patients with drug-naive late-onset TLE.•Patients displayed cognitive deficits including the domains of memory.•Memory deficits may be related to recent seizure frequency and EEG abnormalities. To evaluate cognitive functions including memory in middle-aged and elderly patients with antiseizure drug-naïve late-onset temporal lobe epilepsy (TLE). We performed assessments with the Wechsler Adult Intelligence Scale-III (WAIS-III) and Wechsler Memory Scale-Revised (WMS-R) in 26 antiseizure drug-naïve patients with late-onset TLE, in comparison to 30 healthy subjects. We investigated the relationships between these cognitive function scores and clinical characteristics, seizure frequency, and frequency of interictal epileptic discharges (IEDs). Patients with epilepsy had a significantly lower score than healthy controls in the verbal intelligence quotient (IQ), the performance IQ, and full-scale IQ in intelligence testing. Patients showed significantly decrease in the verbal memory scores, visual memory scores, general memory scores, and delayed recall scores compared with those in the control subjects. Delayed recall scores were significantly negatively correlated with recent seizure frequency and the total IEDs count per minute, but not with age of onset or duration of illness. Patients with antiseizure drug-naïve late-onset TLE displayed cognitive deficits including the domains of memory by using standard clinical neuropsychological test. Patients with late-onset epilepsy need to be considered for cognitive dysfunction at the time of diagnosis of TLE because they may have their daily life and work affected not only by epileptic seizures but also by cognitive deficits. Appearance of seizures and EEG abnormalities may affect the memory function in patients with late-onset TLE.